Malignant Syndrome in Parkinson Disease Similar to Severe Infection - Dong Hun Lee (Korean Journal of Critical Care Medicine, 2017)
A 70-year-old woman with Parkinson disease was admitted to the emergency department with altered consciousness, fever and convulsive movements without experiencing withdrawal from antiparkinsonian medication. Six hours after the emergency department visit, the patient had a hyperpyrexia (> 40°C) and a systolic blood pressure of 40 mmHg. There was no evidence of bacterial infection based on extensive workups. The patient was discharged without aggravation of Parkinson disease symptoms after treatment that included administration of dantrolene sodium, enforcement of continuous renal replacement therapy and cooling blankets. Malignant syndrome should be suspected if high fever occurs in Parkinson disease patients without evidence of a definitive infection.